On the estimation of the rate of convergence in the two-dimensional central limit theorem - Paulauskas, V.; Slušnys, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Паулаускас, А. Слушнис. Оценка скорости сходимости в двумерной центральной предельной теореме V. Paulauskas, A. Slušnys. Konvergavimo greičio įvertinimas dvimatėje centrinėje ribinėje teoremoje